Is Burnout a Missing Link? Exploring the Relationship between Work-Life Balance and Job Satisfaction. - Shafariah, Hanuna; Gofur, Abdul (Oikonomia: Jurnal Manajemen, 2025)
Purpose This study investigated the relationship between work-life balance (WLB), burnout, and job satisfaction, examining the mediating role of burnout. The study aimed to understand how effective WLB contributes to reduced burnout and increased job satisfaction, using the Conservation of Resources (COR) theory as a framework. Methodology The methodology involved a sample of 146 employees from two companies in Jakarta, utilizing stratified proportionate random sampling. Using MacroPROCESS for SPSS model no 4 to analyze the hypoyheses. Findings The results demonstrate that a positive work-life balance significantly reduces burnout levels, which in turn enhances job satisfaction. Furthermore, the study reveals that burnout mediates the relationship between work-life balance and job satisfaction. Suggestion The findings suggest that organizations should prioritize strategies and initiatives that promote work-life balance to mitigate burnout and foster higher levels of job satisfaction among their employees.